Lovely asunder : poems - Deulen, Danielle Cadena, 1979- (University of Arkansas Press, 2011)
Danielle Cadena Deulen is a PhD candidate in English at the University of Utah. Her book of essays, The Riots, is the winner of the 2010 AWP Award Series in Creative Nonfiction and is published by the University of Georgia Press.